High-temperature microstructural evolution of SiCN fibers derived from polycarbosilane with different C/N ratios. Issue 3 (March 2020) - Long, Xin; Shao, Changwei; Wang, Jun; Wang, Yingde
Abstract: Research into the high-temperature microstructural evolution of SiCN ceramic fibers is important for the aerospace application of advanced ceramic matrix composites in harsh environments. In this work, we studied the microstructural evolution of SiCN fibers with different C/N ratios that derived from polycarbosilane fibers at the annealing temperature range of 1400∼1600 °C. These results showed that the phase separation of SiCx Ny phase and the two-dimension grain growth process of free carbon nanoclusters could be processed at the researched temperature range. As the annealing temperature increased to 1600 °C, the crystallization of amorphous SiC and Si3 N4 could be detected. SEM and Raman analysis showed that the decomposition and carbothermal reduction of the Si3 N4 phase at high temperatures played primary roles in contributing to the fiber strength degradation. Thus, a higher C/N ratio, which is beneficial for inhibiting the decomposition of amorphous Si3 N4, helps SiCN fibers retain high tensile strength at high temperatures.